NCT-WES: A new single moderator directional neutron spectrometer for neutron capture therapy. Experimental validation. (27th July 2021) - Bedogni, R.; Lega, A.; Calamida, A.; Monti, V.; Castro-Campoy, A. I.; Menzio, L.; Napolitano, T.; Pola, A.; Bortot, D.; Pietropaolo, A.; Costa, M.; Altieri, S.
Abstract: A directional neutron spectrometer called NCT-WES (Neutron Capture Therapy Wide Energy Spectrometer), conceived as a spectrometric beam monitor in neutron capture therapy, was designed and prototyped. As other types of single moderator neutron spectrometers, NCT-WES condenses the functionality of Bonner Spheres in a single moderator embedding multiple thermal neutron detectors in previously optimized positions. NCT-WES is a polyethylene cylinder with 36 cm diameter and 41.5 cm height. To achieve a sharply directional response, the sensitive part is shielded with a thick barrier made of polyethylene and borated rubber, except in the direction identified by the collimating aperture. The size, geometry, materials and detector locations were previously optimized to emphasise the spectrometric capability in the epithermal range. TNPD-type thermal neutron detectors, consisting of 1 cm 2 silicon p-i-n diodes covered with 6 LiF are used as internal thermal neutron detectors. The simulation model of NCT-WES was experimentally verified by exposing the prototype in the reference neutron field of 241 Am-Be available at the Politecnico di Milano. The count rate in the NCT-WES internal detectors, as calculated from the simulation model, coincided with the experimental ones within about 2%, confirming the high degree of accuracy of the NCT-WES simulation model. Aspects related to the future use of NCT-WES in therapeutic neutron beams are finally discussed.